2014
DOI: 10.1371/journal.pone.0105119
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Management and Vaccination Errors: A Representative Online-Survey among Primary Care Physicians

Abstract: BackgroundEffective immunizations require a thorough, multi-step process, yet few studies comprehensively addressed issues around vaccination management.ObjectivesTo assess variations in vaccination management and vaccination errors in primary care.MethodsA cross sectional, web-based questionnaire survey was performed among 1157 primary physicians from North Rhine-Westphalia, Germany: a representative 10% random sample of general practitioners (n = 946) and all teaching physicians from the University Duisburg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
(21 reference statements)
2
9
1
3
Order By: Relevance
“…Previous studies investigating immunization-related safety incidents mirror our findings and demonstrate receipt of additional vaccines is a widespread problem often resulting from poor documentation e.g. where a child is immunized but this goes undocumented resulting in that child receiving that same vaccine later [4,7,23] . In one U.S. study, over 20% of children received unnecessary duplicate vaccinations [4] .…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies investigating immunization-related safety incidents mirror our findings and demonstrate receipt of additional vaccines is a widespread problem often resulting from poor documentation e.g. where a child is immunized but this goes undocumented resulting in that child receiving that same vaccine later [4,7,23] . In one U.S. study, over 20% of children received unnecessary duplicate vaccinations [4] .…”
Section: Discussionsupporting
confidence: 81%
“…Refrigerators were outside the target range 10.2 % of the total time, with single refrigerators outside the target range for as much as 66.3 % of the time. These results are in line with studies worldwide, which discuss the following key problems related to vaccine storage: 1) temperatures outside the target range [ 10 , 11 ], 2) lack of adequate temperature measurement devices [ 12 14 ], 3) lack of continuous temperature documentation [ 4 , 12 14 ], 4) use of inadequate refrigerators [ 9 , 10 , 12 ], 5) lack of separate refrigerators [ 13 – 15 ], 6) inadequate storage practices [ 2 , 12 , 14 , 15 ], 7) lack of designated personnel [ 14 ], and 8) insufficient staff training and guidance [ 12 , 14 , 16 18 ].…”
Section: Introductionsupporting
confidence: 86%
“…In a cross-sectional web-based questionnaire survey, we analyzed vaccination management among a 10 % random sample of primary care physicians from one of Germany’s largest federal states, North Rhine-Westphalia [ 4 ] using international recommendations for vaccine storage [ 5 – 9 ]. The survey (n = 211) revealed that 16 % of the primary care physicians have experience with cold chain breaches either as an error or near error; 8 % do not regularly control their storage with regard to vaccine wrapping, vaccine expiration date, and refrigerator temperature; 49 % do not keep a storage temperature log; and 21 % fail to use a separate refrigerator solely for vaccine storage.…”
Section: Introductionmentioning
confidence: 99%
“…Erste Auswertungen dieser Querschnittsstudie, bei der zunächst die Antworten der Ärzte aus der Zufallsstichprobe und der Lehrärzte aus NRW analysiert wurden, zeigten ein gutes Impfmanagement bei 19 % der Praxen. Da die STI-KO-Empfehlungen keine detaillierten Hinweise zum Impfkühlschrank und Impfstoffmanagement beinhalten, wurde zur Bewertung ein von uns anhand US-amerikanischer, britischer und australischer Vorgaben [15][16][17][18][19], 3 Praxisbesuchen und der medizinischen Literatur erstellter Kriterienkatalog zur Impfstoff-, Patienten-, Personal-und lagerungsbezogenen Qualität zugrunde gelegt [20].…”
Section: Hintergrundunclassified
“…Dies ist insbesondere von Bedeutung, da Auswertungen der US Fehlerdatenbank "MEDMARX" ergeben haben, dass der "falsche Impfstoff" mit 25 % der am häufigsten aufgetretene Impffehler war und ursächlich meist eine namentlich bedingte Verwechslung mit anderen Impfstoffen ist [29]. In unserer Studie gaben 30 % der Ärzte an, dass in ihrer Praxis schon einmal ein falscher Impfstoff geimpft wurde [20]. Eine besondere Schwierigkeit ergibt sich durch die Tatsache, dass unterschiedliche Marken des gleichen Impfstoffs z. T. unterschiedliche Impfschemata haben.…”
Section: Praxisinterne Aufgabenverteilung Für Impfstoffauswahl Beschunclassified